Glycan dysregulation as one of major metabolic subtypes is associated with TERC overexpression and poor outcomes in cervical cancer - Dong, Yanlei; Zhang, Xinyuan; Zhao, Jingjie; Hou, Qingzhen; Yu, Yunhai; Wu, Yu; Shi, Xing; Wang, Lina; Xu, Dawei (Frontiers in Immunology, 2025)
BackgroundMetabolic reprogramming is an important hallmark of cervical cancer (CC), and extensive studies have provided important information for translational and clinical oncology. Here we sought to determine metabolic association with molecular aberrations, telomere maintenance and outcomes in CC.MethodsRNA sequencing data from TCGA cohort of CC was analyzed for their metabolic gene expression profile and consensus clustering was then performed to classify tumors into different groups/subtypes. The reproducibility of the classification system was further evaluated in GSE68339 CC cohort. The association of metabolic groups with clinical characteristics, telomere maintenance and somatic alterations was assessed to define molecular features of each subtype. Finally, the metabolomic analyses were carried out to directly measure metabolites in tumors and their non-tumorous adjacent tissues (NTs) from 10 CC patients using ultra performance liquid chromatography-mass spectrometry (UPLC-MS).ResultsThe analysis of 2752 metabolism-related gene expression in TCGA 304 CC tumors showed a significant expression heterogeneity of these genes. Consensus clustering of these CC tumors identified three distinct metabolic groups (MG), with MG1, MG2 and MG3 characterized by dysregulations in glycans, amino acids/carbohydrates and lipids, respectively. Patients within the MG1 subtype had the shortest disease-free survival (DFS) coupled with robust TERC overexpression. This metabolic stratification was validated in the GSE68339 CC cohort. We further developed a 3 glycan-related gene model (GRGM-3) as a predictor for patient DFS. The TCGA patients were divided into risk-Low and High groups based on their tumor GRGM-3 score using a median cutoff, and those in the risk-High group had significantly shorter DFS. When combined with TERC expression, patients in the high-risk group with high TERC levels had the shortest DFS. Finally, we analyzed metabolites in tumors and NTs from 10 CC patients and further confirmed the metabolic dysregulations identified by gene expression profiling.ConclusionMetabolic heterogeneity occurs substantially in CCs and glycan dysregulation is associated with the shortest DFS in CCs. Specifically, the combination of GRGM-3 scores with TERC expression identifies patients with the poorest outcomes, providing a potential tool for individualized risk assessment and contributing to CC precision medicine. It is worth validating our findings for potential clinical application.